Komputasi Paralel GPU Dengan Teknologi Nvdia Cuda Untuk Enkripsi Berkas Pdf Menggunakan Algoritma RC4 DAN MD5 - Al Farissi; Samatra Marwa Hany; Rifkie Primartha (Jurnal Sistem Informasi, 2017)
AbstractOne way to secure files on storage media is by cryptographic techniques.The content of PDF files sometimes Contains with important information. therefore information security becomes a priority at this time. In this research, PDF files will be encrypted with MD5-RC4 technique. This combination makes information more secure and protected from information disclosure. This research implement parallel computing using GPU and CPU that make a performance of process run faster. When Nvidia released CUDA, GPU Become a strong power as an efficient accelerator for complex computations. Therefore, the GPU with CUDA and the comparision between CUDA and CPU will be discussed in this study.Keywords: PDF, Enkripsi,CUDA,MD5,RC4.